Challenges and Opportunities for Women and Girls in Adaptation to the Climate Change Action Plan 2021-2030: A Case Study in Mekong Delta, Vietnam - Duong Van Thanh; Vu Hai Truong; Nguyen Tan Phat (Tạp chí Khoa học Xã hội và Nhân văn (VNU Journal of Social Sciences and Humanities), 2025)
Vietnam is one of many countries heavily impacted by climate change in recent decades. The Mekong Delta region has been a prominent example of the severity of climate change on agriculture and ecosystems. Many studies have been conducted to assess the impacts of climate change on different sectors in Vietnam, however, there are gaps in understanding climate effects from a gender perspective and the important role gender plays in climate response and adaptation. This paper aims to use a gender-specific perspective to examine effects of climate change on women’s and girls’ livelihoods, water and food security, labor and income, migration and education in Hoa An commune, Hau Giang province in Mekong Delta. Particularly, this paper addresses challenges that women and girls face amidst impacts of climate change. It also discusses opportunities to empower women and young girls in which education and training on raising awareness of climate change and taking appropriate adaptation measures, play a significant role. The paper is structured through the discussion of the theoretical background that employs a gender lens to frame climate change within the context of Mekong Delta in Vietnam. The methodology section describes the study site in Hoa An commune of Hau Giang province in the delta. Mixed qualitative and quantitative methods were adopted during the data collection process. The results report on (1) gender roles and gender power at family and at work (2) vulnerability perceived by women and girls, (3) impacts caused by climate change (4) livelihood support from central and local governments, adaptation, and role of education. Received 16th June 2022; Revised 10th August 2022; Accepted 25th August 2022